Multiparticulate oral formulations as a viable strategy for precise drug dosing in pediatrics: propranolol case study - Kurćubić, Ivana; Cvijić, Sandra; Lukić, Milica; Ibrić, Svetlana; Djuriš, Jelena (Archives of Pharmacy, 2021)
The development of solid dosage forms that are both convenient for administration and allow precise drug dosing for pediatric patients is one of the great challenges in contemporary pharmaceutical technology. The presented study has utilized propranolol hydrochloride, as one of the most frequently prescribed drugs that require manipulation of the conventional dosage forms to be administered to children. Multiparticulate oral formulations, powder- and granule-filled capsules, as well as mini tablets, were prepared and characterized in terms of their mass and content uniformity and compared to conventional marketed tablets split into halves and quarters. The obtained results have demonstrated the superiority of the multiparticulate formulations, in terms of their average mass and drug content uniformity. It has also been demonstrated that, due to improved flowability, granule-filled capsules are more conveniently compounded and provide higher content uniformity compared to powder-filled capsules. The presented compounding method could be easily employed in community pharmacy settings. Mini tablets with high and uniform content of propranolol hydrochloride have been successfully prepared, thereby presenting a viable strategy for efficient drug dose adjustment.
Keywords: Propranolol; pediatric dosage forms; multiparticulates; mini tablets; uniformity of content